The neuroregulation of food intake: The effect of sex on meal selection patterns and the influence of diet on central H1 receptor binding in female SD rats - Mercer, Preston; Bundrant, Holly M.; Saxon-Kelley, Danita; Haq, Akram-ul; Robinson, Erica N. (Journal of Pediatric Biochemistry, 2013)
Obesity is a growing health problem because it is associated with many diseases, such as cancer, heart disease and diabetes. There is increasing evidence that obesity is under control of several factors in the brain, including orexigenic and anorexigenic neuropeptides and neurotransmitters. Histamine-containing neurons and their receptors, closely involved in regulation of food intake, are distributed throughout the brain. In the reported experiments, dietary influence on H1-receptor binding was examined using female Sprague-Dawley rats fed diets of low, medium or high quality protein, or diets of normal energy, low energy, very low energy. Differences in food intake and weight change occurred; with no significant differences in whole-brain H1 receptor binding such as had been seen in male rats. Histaminergic antagonism was then tested using centrally acting antihistamines. Weight gain was related to dietary protein intake for saline and doxepin treated rats. Rats fed 5% protein (maintenance) demonstrated that doxepin was a more effective histaminergic antagonist than terfenadine (peripherally acting) in affecting mean cumulative weight gain and food intake. Dietary protein level influenced observed outcomes for the two groups. Male and female rats were given the choice of diets containing 0% or 60% protein, with or without doxepin. Females chose cumulatively lower protein intake than males. The relationship between dietary content, the histaminergic system and food intake in female rats appears to be different than that seen previously in male rats while Zucker obese rats showed no response in histaminergic binding. These studies support the observation that centrally acting antihistamines can increase weight gain.
Keywords: Histamine receptor; obesity; rat; dietary protein